University teachers' training and its influence on professional development - Katia Caballero Rodríguez (Universitat Politècnica de València, 2013)
The University Faculty profile is defined and transformed by the demands that evaluation and incentive systems establish for those wishing to gain access to and promotion within the profession. In this regard, university teachers' training is a key factor in creating this profile and contributing to the development of a particular professional identity. The aim of this article is to determine how different types of training are influencing the development of the professional activity that university teachers carry out and to analyze if there are significant differences in responses based on certain descriptive variables (gender, age, scientific branch, academic rank, etc.). This work, which is part of a wider research project, combines the use of quantitative methodology, through a survey, and qualitative methodology, through the biographical-narrative interview. The results obtained show that continuous training has greater influence on professional development than initial training, because the latter is practically non-existent, especially in teaching. Also, according to various descriptive variables, significant differences in university teachers' responses have been perceived. The conclusions lead us to highlight the need to consider systems of training appropriate to the evaluation's requirements, especially during the preliminary and initial phase of the career. And, also, it urges departments to offer more training support to university teachers, transforming them into learning communities.